2020
DOI: 10.1007/s40123-020-00298-y
|View full text |Cite
|
Sign up to set email alerts
|

Slowing the Progression of Myopia in Children with the MiSight Contact Lens: A Narrative Review of the Evidence

Abstract: Myopia has become a major public health problem in the world due to the increase in its prevalence in the past few decades and due to sight-threatening pathologies associated with high myopia such as cataracts, glaucoma and especially myopic maculopathy. This article is a narrative review of the evidence that currently exists on a contact lenses (CLs) specifically designed to correct myopia and to slow its progression. To contextualise the topic we discuss the different classifications and definitions that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…The continuous progression of myopia will have a series negative effects [24]. As the loss of vision caused by high myopia is irreversible, myopia have become one of the main causes of untreated vision loss in the world [25]. The axis is an important monitoring index of myopia [21].…”
Section: Discussionmentioning
confidence: 99%
“…The continuous progression of myopia will have a series negative effects [24]. As the loss of vision caused by high myopia is irreversible, myopia have become one of the main causes of untreated vision loss in the world [25]. The axis is an important monitoring index of myopia [21].…”
Section: Discussionmentioning
confidence: 99%
“…MiSight's daily lens product was FDA-approved in 2019 for SCLs that slow myopia in children while correcting vision using a concentric ring design. [376,377] According to the NIH, the clinical approval period for this SCL was six years. Another SCL device on the market is the SENSIMED Triggerfish®, which performs intraocular pressure sensing and received FDA approval in 2017.…”
Section: Challenges Of Smart Contact Lensesmentioning
confidence: 99%
“…MiSight Contact Lens (CooperVision) is the first lens approved by the U.S. Food and Drug Administration (FDA) to control the progression of myopia in children ( 21 ). Randomized clinical trial (RCT) results showed that MiSight is safe and effective in slowing the progression of myopia over 2 ( 21 ) to 3 years ( 22 ).…”
Section: Current Interventionsmentioning
confidence: 99%
“…MiSight Contact Lens (CooperVision) is the first lens approved by the U.S. Food and Drug Administration (FDA) to control the progression of myopia in children ( 21 ). Randomized clinical trial (RCT) results showed that MiSight is safe and effective in slowing the progression of myopia over 2 ( 21 ) to 3 years ( 22 ). Orthokeratology (Ortho-K), approved by the FDA in May of 2021, are a series of hard, hydrophilic, gas-permeable contact lenses designed to gradually flatten the central cornea.…”
Section: Current Interventionsmentioning
confidence: 99%